Karakteristik Teh Daun Bambu Tali (Gigantochloa apus Kurz.) pada Metode Blansir dan Suhu Pengeringan - Dewi, I Gusti Ayu Krisna; Wrasiati, Luh Putu; Ganda Putra, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Bambu Tali leaves are part of bamboo plants that have not been used optimally. Bambu Tali leaves can be used as a refreshing drink. The aims of this study is to determine the effect of blanching and drying temperature on the characteristics of the Bambu Tali leaves and to determine method of blanching and drying temperature which can produce the best characteristics of Bambu Tali tea leaves. This study used a Randomized Block Design with two factors. The first factor’s is the blanching method that is without blanching, steam blanching, and water blanching. The second factors that is drying temperature that consisting of 50 o C, 60 o C, and 70 o C. Data were analyzed by analysis of variance and continued with Tukey test. The results showed that the blanching treatment and drying temperature significantly affected the water content, ash content, extract content in water, total phenolic, IC 50 , and organoleptic test. The steam blanching treatment with a drying temperature of 70 o C is the best treatment to produce Tali’s bamboo tea leaves with a characteristics of water content is  5.17%, ash content is 5.52%, extract content in water is 35.70%, total phenolic is 36.92 mg GAE/g, and antioxidant activity of IC 50 2,629.06 ppm, and color scoring of sensory evaluation is 3.55 (yellowish green to green), taste scoring is 3.55 (slightly astringent to astringent), Scent scoring of 3.45 (slightly leaf scent to leaf scent), and overall reception 4.90 (rather like). Keywords: Gigantochloa apus Kurz., blanching, drying temperature, tea.